PENGARUH JARAK TANAM DAN MACAM PUPUK DAUN TERHADAP PERTUMBUHAN DAN PRODUKSI KACANG HIJAU (Paseolus radiatus L.) - Suharso, - (Universitas Islam Darul Ulum, 2009)
The purpose of this study is to determine the effect of spacing and range of foliar fertilizer on growth and production of green beans (Pasealus radiatus L.). This research used randomized block design (RBD) factorial consisting of two factors and each factor consists of three levels, namely: Factor I: Spacing (A) with three levels: A1: Plant spacing 20 cm x 20 cm; J2: Plant spacing 20 cm x 25 cm; J3: Plant spacing 20 cm x 30 cm; Factor II: foliar fertilizer dose (D); D1: Gandapan 2 grams / liter of water; D2: Polar 2 ml / liter of water; D3: Atonik 2 ml liter water. The research concluded that there is interaction between spacing treatments and kinds of fertilizers on the variable number of leaves, leaf age 14 dap, 21 dap, 28 dap and 49 dap; number of pod age of 42 dap and 49 dap; age 60hst dry pod weight, seed dry weight age 60 dap; and 1000 grain weight of dry seed age 60 dap. The real difference between the treatment plant spacing and variety of foliar fertilizer on plant height variable age of 14 dap, 21 dap, 28 dap, 35 dap, 42 dap and 49 dap; number of leaf age of 35 dap and 42 dap; number of branches the age of 28 dap, 35 dap, 42 dap and 49 dap; best result of interaction occurs in the combined treatment plant spacing of 20 cm x 25 cm with a foliar fertilizer polar 2 ml / lt of water (J2D2).